Ratu-Ratu Aceh Abad ke-17 M - Rd. Siti Sa'adah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
The women government (power) in Aceh Darussalam Sultanate had happened for almost 60 years by four women sultanah from 1641-1699 AD. They are Sultanah Tajul Alam Safiatuddin Syah (1641- 1675). Sultanah Nurul Alam Nagiatuddin Syah (1675- 1678), Sultanah Inayat Zakiatuddin Syah (1678-1688), and Sultanah Kamalatuddin Syah (1689-1699). There are many factors caused the sultanah raising to the power in Aceh, some of them are the particular situation and condition, such as no prince crown born.